2020
DOI: 10.1021/acsapm.9b01238
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Methodology Design for Biobased and Sustainable Coatings for Water- and Oil-Resistant Paper

Abstract: Reported herein is the synthesis of biobased and sustainable chitosangraf t-castor oil (CHI-g-CO)copolymer that can be used for paper coating. CHI-g-CO was obtained via chemical grafting of castor oil-capped isocyanate (CO-capped-NCO) onto a chitosan polymer backbone. The CHI-g-CO copolymer was then employed as a waterborne coating for Kraft unbleached paper to render the coated paper both water-and oil-resistant. The formulation of the CHI-g-CO-coated paper was optimized by using the response surface methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Taking coating materials as an example, the properties of biobased coatings must be improved, particularly their mechanical strength and water resistance. [5][6][7] One approach to build new functionality and improve performance is to fabricate biobased nanocomposites. [8][9][10][11] Nanoparticles have already been widely used to enhance the performance of the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Taking coating materials as an example, the properties of biobased coatings must be improved, particularly their mechanical strength and water resistance. [5][6][7] One approach to build new functionality and improve performance is to fabricate biobased nanocomposites. [8][9][10][11] Nanoparticles have already been widely used to enhance the performance of the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the p-values were determined to analyze model fits and a comparison of F-values were analyzed to discover the effect of variables on the response. [23] 3 | RESULTS AND DISCUSSION…”
Section: Box-behken Designmentioning
confidence: 99%
“…Syeda et al [10] showed that the chitosan coated paper had a kit rating value of 12/12 when the coating load was 6.1 g/m 2 , and the chitosan-graft-polydimethylsiloxane coated paper obtained the eighth grade when the coating load was 9.4 g/m 2 . Zhao et al [18,19] reported that the chitosan coated paper had a kit rating value of 8/12 when the coating load was 9.33 g/m 2 . They further employed chemically modified chitosan in combination with polydimethylsiloxane and castor oil, respectively, and the kit rating values of coated papers were 12/12 and 10/12 when the coating loads were 10.33 g/m 2 and 4.3 g/m 2 .…”
Section: Introductionmentioning
confidence: 99%